Penerapan Media Time Dominoes Berbasis Model Pembelajaran Kooperatif Tipe Jigsaw untuk Meningkatkan Hasil Belajar Peserta Didik Kelas IV - Az Zahra, Salsabila; Purwati, Panca Dewi (Nanggroe: Jurnal Pengabdian Cendikia, 2024)
Improving student learning outcomes can be achieved through learning that applies innovative and creative learning models and media. One learning model that can be used is the Jigsaw type cooperative learning model with Time dominoes media. The purpose of this research is to determine the application of learning using the Jigsaw type cooperative model and to determine the effectiveness of the application of the Jigsaw learning model assisted by time dominoes media in clock reading material and daily activities. This research uses a qualitative descriptive research method. Data collection instruments were carried out using observation, interviews and tests. Based on the research results, the application of the Jigsaw learning model assisted by time dominoes media on clock reading material and daily activities was able to improve learning outcomes with learning outcomes in the pretest reaching 46.6 with a percentage of students achieving completeness of 33.3%, of which 18 students only 6 completed. Meanwhile, the learning outcomes in the posttest reached 84.4 and the percentage of students who completed was 77.7%, where of the 18 students, 14 students had passed.